Diagnóstico socioeconómico de los comerciantes informales en la ciudad de Naranjito en el sector de la Avenida 5 de Octubre y 10 de Agosto provincia del Guayas Ecuador - Mendoza Romero, Samuel David (2022)
The results presented analyze the social and economic situation of informal merchants on Avenue 5 de October and 10 de August in the city of Naranjito, province of Guayas, as a general objective of the research. The conditions of these people at the time of undertaking informal work were extremely complex as they could not afford the expenses in their own primary needs and that of the family. The research process was developed from a mixed approach with the use of the collection, processing and analysis of numerical and qualitative data regarding criteria, experiences and theories, which made it possible to understand the phenomenon studied; the scope is descriptive with the presentation of the elements necessary to diagnose this situation, obtained through the application of the techniques of the survey and the unstructured interview. The results reveal that these are mostly young adults with a high school level who, on average, maintain a large family, present difficulties in carrying out their activity as they face possible capital shortages, reduction of clients and municipal control; without possibilities of reaching a condition of formality. In general, the situation of informal traders is unsatisfactory with little prospect of transformation. The relevance of the study is proven, mainly because it focuses on a problem of the human being; hence, informal work is considered by international, regional and national legal regulations; as well as proposals prepared by the ILO, WB and ECLAC.